Smart Responsive Nanoformulation for Targeted Delivery of Active Compounds From Traditional Chinese Medicine - Jiang, Xuejun; Lin, Mei; Huang, Jianwen; Mo, Mulan; Liu, Houhe; Jiang, Yuan; Cai, Xiaowen; Leung, Wingnang; Xu, Chuanshan (Frontiers in Chemistry, 2020)
Traditional Chinese medicine (TCM) has been used to treat disorders in China for ~1,000 years. Growing evidence has shown that the active ingredients from TCM have antibacterial, antiproliferative, antioxidant, and apoptosis-inducing features. However, poor solubility and low bioavailability limit clinical application of active compounds from TCM. “Nanoformulations” (NFs) are novel and advanced drug-delivery systems. They show promise for improving the solubility and bioavailability of drugs. In particular, “smart responsive NFs” can respond to the special external and internal stimuli in targeted sites to release loaded drugs, which enables them to control the release of drug within target tissues. Recent studies have demonstrated that smart responsive NFs can achieve targeted release of active compounds from TCM at disease sites to increase their concentrations in diseased tissues and reduce the number of adverse effects. Here, we review “internal stimulus–responsive NFs” (based on pH and redox status) and “external stimulus–responsive NFs” (based on light and magnetic fields) and focus on their application for active compounds from TCM against tumors and infectious diseases, to further boost the development of TCM in modern medicine.